Liver disease in patients with cystic fibrosis. Issue 3 (May 2018) - Kamal, Natasha; Surana, Pallavi; Koh, Christopher
Abstract : Purpose of review: The aim of this study was to provide an overview of the current understanding of the pathophysiology, diagnosis and management of cystic fibrosis-liver disease (CFLD). Recent findings: CFLD has a variety of manifestations. Previously, it was thought that patients progressed from mild cholestatic disease to cirrhosis to decompensated cirrhosis with portal hypertension. Newer evidence suggests that some patients may develop cirrhosis while others develop noncirrhotic portal hypertension. Advances in our understanding of the pathophysiology of disease necessitate modifications to the current diagnostic criteria. Both fibroscan and noninvasive biomarkers can be used to identify patients with cirrhosis and portal hypertension. Ursodeoxycholic acid remains the mainstay of therapy despite a paucity of rigorous studies supporting its use. Novel therapeutic agents such as CF transmembrane conductance regulator (CFTR) modulators and potentiators are encouraging but need to be evaluated specifically in CFLD. Summary: A better understanding of the pathophysiology of disease is critical to developing more disease-specific diagnostics and therapeutics.